2007
DOI: 10.1002/mrc.2154
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbonyl group in the asymmetry of 3, 4JCH coupling constants in norbornanones

Abstract: A rationalization of the known difference between the 3,4JC4H1 and 3,4JC1H4 couplings transmitted mainly through the 7-bridge in norbornanone is presented in terms of the effects of hyperconjugative interactions involving the carbonyl group. Theoretical and experimental studies of 3,4JCH couplings were carried out in 3-endo- and 3-exo-X-2-norbornanone derivatives (X = Cl, Br) and in exo- and endo-2-noborneol compounds. Hyperconjugative interactions were studied with the natural bond orbital (NBO) method. Hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
8
0
2
Order By: Relevance
“…Doubtless, the ‘acetaldehyde effect’ is one of the main effects leading to the differences between 2 J C 3 H 2 and 2 J C 2 H 3 SSCCs in furan ( 1a ) and in pyridine ( 2b ), since in both cases only the former SSCC is contributed to by that effect. It is noted that a somewhat similar effect was reported recently,36 where the carbonyl group in norbornanones yielded a difference in 3, 4 J CH SSCCs.…”
Section: Fc Term For Ssccsupporting
confidence: 82%
“…Doubtless, the ‘acetaldehyde effect’ is one of the main effects leading to the differences between 2 J C 3 H 2 and 2 J C 2 H 3 SSCCs in furan ( 1a ) and in pyridine ( 2b ), since in both cases only the former SSCC is contributed to by that effect. It is noted that a somewhat similar effect was reported recently,36 where the carbonyl group in norbornanones yielded a difference in 3, 4 J CH SSCCs.…”
Section: Fc Term For Ssccsupporting
confidence: 82%
“…The carbonyl group has shown to play a driving role in the through-the-bridge 3 J C,H couplings (actually 3,4 J C,H couplings) in norbornanone, in which a σ C3 -C4 → σ * C2=O interaction defines an additional coupling pathway for 3,4 J C4,H1 , but not for 3,4 J C1,H4 ; consequently, the former coupling constant was found to be significantly larger than 3,4 J C1,H4 . [12] Since the conformational isomerism of 2-bromocyclohexanone is expected to be governed by orbital interactions, especially those involving the π * C=O orbital, in addition to steric and electrostatic interactions, the investigation of the origins of the through-carbonyl long-range 4 J H2,H6 coupling must provide an experimental insight about the hyperconjugation role in this model system. To corroborate the 1 H NMR findings, theoretical approaches were applied to rationalize the results.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that in mono-and di-fluoro-1,1,2,2,9,9,10,10-octafluoro [2.2] paracyclophane (fluoro-AF4s), a bridge fluorine couples with a large coupling constant (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) with the aromatic fluorine ortho and syn, and with a somehow smaller constant (20-10 Hz) with the aromatic fluorine which is pseudo-gem to the fluorine ortho and syn. [2] The other large couplings used for the assignment were the ortho coupling of the aromatic fluorines, 28-18 Hz, significantly larger than the meta or para couplings, 12-0 Hz.…”
Section: Methodsmentioning
confidence: 99%